Cost-Utility Analysis of Chuna Manual Therapy and Usual Care for Chronic Neck Pain: A Multicenter Pragmatic Randomized Controlled Trial - Ha, In-Hyuk; Kim, Eun-San; Lee, Sook-Hyun; Lee, Yoon Jae; Song, Hyun Jin; Kim, Younhee; Kim, Koh-Woon; Cho, Jae-Heung; Lee, Jun-Hwan; Shin, Byung-Cheul; Lee, Jinho; Shin, Joon-Shik (Frontiers in Medicine, 2022)
This study aimed to compare the cost-effectiveness of manual therapy and usual care for patients with chronic neck pain. A cost-utility analysis alongside a pragmatic randomized controlled trial was conducted in five South Korean hospitals. Data were procured from surveys and nationally representative data. Participants were 108 patients aged between 19–60 years, with chronic neck pain persisting for at least three months and a pain intensity score of ≥ 5 on the numerical rating scale in the last three days. The study was conducted for one year, including five weeks of intervention and additional observational periods. Participants were divided into a manual therapy (Chuna) group and a usual care group, and quality-adjusted life-years, costs, and the incremental cost-effectiveness ratio were calculated. The quality-adjusted life-years of the manual therapy group were 0.024 higher than that of the usual care group. From the societal perspective, manual therapy incurred a lower cost—at $2,131—and was, therefore, the more cost-effective intervention. From a healthcare system perspective, the cost of manual therapy was higher, with an incremental cost-effectiveness ratio amount of $11,217. Manual therapy is more cost-effective for nonspecific chronic neck pain management from both a healthcare system and societal perspective.